Evaluation of Cold Chain Management Performance for Temperature-Sensitive Pharmaceuticals at Public Health Facilities Supplied by the Jimma Pharmaceuticals Supply Agency Hub, Southwest Ethiopia: Pharmaceuticals Logistic Management Perspective Using a Multicentered, Mixed-Method Approach. (14th September 2021) - Feyisa, Diriba; Jemal, Awol; Aferu, Temesgen; Ejeta, Fikadu; Endeshaw, Alem
Abstract : Background . Effective and efficient cold chain management maximizes utilization of healthcare resources, reduces cold chain products wastage, and improves the quality of health services. It eventually guarantees that clients receive cold chain products they need at service delivery points. The objective of this study was to evaluate cold chain management performance for temperature-sensitive medicines at public health facilities in Southwest Ethiopia supplied by the Jimma Pharmaceuticals Fund and Supply Agency hub. Method and Materials . The study used an institution-based cross-sectional study design. Forty-seven (47) public health facilities in Southwest Ethiopia were evaluated using checklists adopted from the Logistic Indicators Assessment Tool, Vaccine Management Assessment Tool, and Logistic System Assessment Tool. Results . The study revealed that the mean availability of essential cold chain products was 72.1 ± 14.8% while the average stock-out rate was 26.2 ± 8.6%. The median stock-out duration was 23 ± 21 days for all visited public health facilities. Two hundred and sixty-three (43.06 ± 15.3%) of the public health facilities' stock records were found accurate, and the wastage rate due to expiration was 9.2 ± 7.8% for all visited health facilities. Thirty public health facilities (63.8 ± 36.2%) had acceptable storage conditions. Conclusions and Recommendations . Supply chain performance at the study facilities was not adequate overall, and focused efforts need to be directed at managing the availability of critical cold chain medicines. Some cold chain management challenges demand the attention of the top management, while the rest can be addressed by operational management at the facilities through provision of appropriate training and supervision of the cold chain pharmaceutical handlers.